Sistem Pendukung Keputusan Dalam Menentukan Dosen Favorit Menggunakan Metode Profile Matching - Silvya Ajeng Saraski; Akhyarari Nanda Lubis2; R. Putri Angela Parapak (Jurnal Teknologi dan Sistem Informasi, 2022)
Based on the Law of the Republic of Indonesia number 20 of 2003, educators are educational staff who are qualified to become teachers, lectures, counselors, tutors, facilicators and other designations according to their specificity, and participate in the implementastion of eduaction. Educators are professional personnel in charge of planning and implementing the learning process assessing the impact of learning, providing guidance and coaching, especially for eduactions in higher education. Decision Support System for the Determination of Favorite Lecturer Selection of Students is a system that can increase the ease in decision making in determining Lecturers which will make lecturers to be more enthusiastic in teaching and students can also be enthusiastic in following the lessons being taught. Profile matching is a method used to support a decision support system that will be carried out by utilizing various aspects that will be used as a source of assessment carried out by students.